Insight on microscopic mechanisms of CH4 and CO2 adsorption of coal with different ranks. (15th December 2022) - Sun, Yiwei; Wang, Liang; Wang, Ruixue; Zheng, Siwen; Liao, Xiaoxue; Zhu, Zibin; Zhao, Yuchen
Highlights: Clarified that micropores were the main adsorption sites. Functional groups indirectly affected the adsorption capacity by affecting micropores evolution. The adsorption of CO2 and CH4 in low-rank coal showed the maximum adsorption difference. Abstract: By conducting research on the microscopic mechanisms of CH4 and CO2 adsorption in different rank coals, the CO2 -enhanced coal bed methane recovery (CO2 -ECBM) technique can be further developed. In this paper, low-pressure N2 adsorption (LPGA-N2 ), low-pressure CO2 adsorption (LPGA-CO2 ), isothermal adsorption, Fourier transform infrared (FTIR) experiments, and molecular simulations were applied to analyze the mechanisms. The results demonstrated that the pore volume and specific surface area (SSA) of coal showed a U-shaped trend with the increase of metamorphic. The volume and SSA of the micropore were positively correlated with the ultimate adsorption volume, indicating that micropores were the main sites for adsorption. With the increased metamorphic degree, the aliphatic chains and oxygenated functional groups shed, and the aromatic rings polymerized. These changes in chemical functional groups directly affected the adsorption capacity of coal and indirectly affected the adsorption capacity by affecting micropore evolution. Compared with the CH4 molecule, the CO2 molecule had a smaller structure and a stronger intermolecular force, shown as the larger adsorption energy and closer distance to the coal molecule in the molecular simulation. These findings can provide the data and theoretical basis for the CO2 -ECBM technique, coal bed methane extraction, and effect evaluation of extraction.